ANALISIS REMOVAL SCALING SILIKA PADA JALUR RE-INJEKSI BRINE PEMBANGKIT LISTRIK ENERGI PANAS BUMI DENGAN MENGGUNAKAN ASAM FLUORIDA - Adhi Setiawan; Deris Eko Saputro; Agung Nugroho (2477 - 6165, 2017)
Silica scale formation on the brine re-injection lines of geothermal power plants can lead to serious problems because it increased pressure drop and failure of the safety devices. One of the most effective methods to solve the problem is acidification of silica scaling using hydroflouric acid (HF). HF has a unique characteristic that is highly reactive with SiO2, easily obtained in the market and cheap. The use of HF can increase the rate of material corrosion in re-injection lines material. The use of HF should be adjusted to the appropriate concentration so it can dissolve silica scale optimally without shortening its life service. The concentration of HF used in the experiment were 5, 10, and 15% wt. The results showed that the optimum concentration of HF in dissolving silica at 15%. This is due to its ability to dissolve the crust mostly greatest than most other concentration that is equal to 21% of the total dissolved silica. The rate of corrosion on the material re-injection line with a concentration of 15% is equal to 0.647 mm/y and provide about 4.63 years life time of pipe.